2010
DOI: 10.1089/dia.2009.0181
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Exhaled Gas Profiles Between Patients with Type 2 Diabetes and Healthy Controls

Abstract: These results suggest that it is possible to separate patients with diabetes mellitus type 2 from healthy controls by multivariate analysis of exhaled endogenous VOCs. This is a first step towards the development of a noninvasive test using breath gas of at-risk persons and making it an attractive option for large-scale testing of at-risk populations. However, the establishment of exhaled volatiles as metabolic markers requires additional confirmatory investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 31 publications
0
35
0
9
Order By: Relevance
“…Consequently, breath acetone concentration could distinguish between patients with diabetes and healthy patients. Greiter et al [30] identified eight VOCs to distinguish between patients with insulin-treated type 2 diabetes and healthy patients. Other authors showed a linear relationship between haemoglobin A 1c , breath acetone, and blood glucose in type 1 diabetes, which is contrary to expectations based on normal physiological conditions [31].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, breath acetone concentration could distinguish between patients with diabetes and healthy patients. Greiter et al [30] identified eight VOCs to distinguish between patients with insulin-treated type 2 diabetes and healthy patients. Other authors showed a linear relationship between haemoglobin A 1c , breath acetone, and blood glucose in type 1 diabetes, which is contrary to expectations based on normal physiological conditions [31].…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason could be related to the ketoacidosis phenomenon associated with poorly controlled diabetes. In fact, several hundred volatile compounds are detected in exhaled breath and many of which represent byproducts of endogenous biological process [26]. Recent studies suggest that integrated analysis of exhaled air in diabetic patients has the potential to serve as a marker of blood glucose level [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to associating specific compounds with physiological processes (Table 1), experiments have also focused on diabetic screening. Using proton transfer reaction-mass spectrometry on 8 mass ranges of exhalates, each representing an unknown group of VOCs, Greiter et al distinguished patients with T2DM from healthy controls with a 90% sensitivity and 92% specificity[96]. Similarly, Kulikov et al found light hydrocarbons (C2-C3 including ethanol and acetaldehyde) to be elevated in the exhaled breath of women who had risk factors for T2DM (i.e.…”
Section: Breath Testing For Diabetes Mellitusmentioning
confidence: 99%